Effects of soil physical properties on geothermal energy transfer - BENNACEUR Djihad (Université de Mostaganem, 2025)
Geothermal energy is a promising renewable resource, but its efficiency depends on the thermal properties of the soil. This study examines heat transfer in unsaturated soils, focusing on soil type, porosity, density, and salinity, using a numerical hydrothermal model for the Oran and Adrar regions of Algeria. The results show that clay-rich soils with low porosity and high density retain heat better, making them ideal for geothermal applications. Salinity also plays a role, with moderate salinity (C = 0.1 M) improving thermal performance in sandy soils, while higher salinity (C = 0.2 M) enhances heat retention in sandy loam. Another key finding is that soil temperature stabilizes at shallow depths (~8m), except when an external heat source is present. These observations are crucial for geothermal transfer, as selecting the ideal soil characteristics can increase the effectiveness of heat extraction. Future research should refine numerical models for heat exchangers, incorporate water vapor transport into heat transfer simulations, and validate findings with experimental data. This study provides valuable guidance for optimizing geothermal energy systems, with practical applications in renewable energy, climate adaptation, and sustainable construction.
Keywords: Geothermal energy; heat transfer; soil-atmosphere interaction; thermal conductivity; porosity; salinity.